Bordetella Pertussis Antibody Levels in DPT/Pentavalent Immunized Preschool Nigerian Children: A Cross-Sectional Study - Bassey, Glory Ekpo; Ekanem, Emmanuel Eyo; Okpara, Henry Chima; Eyong, Komomo Ibor (Journal of Pediatric Infectious Diseases, 2020)
Pertussis is a vaccine-preventable disease and antibodies formed are known to decline with time. The aim of this study was to measure Bordetella pertussis/toxin immunoglobulin G (IgG) antibodies in different age groups of Nigerian children and determine the age at which booster dose may be required. A total of 422 children, aged 6 to 60 months, were tested for the presence of B. pertussis/toxin IgG antibodies by ELISA (enzyme-linked immune sorbent assay). The highest positivity rate was in the 6 to 11 months of age group, while the highest negativity rate was in the age group of 24 to 35 months. We conclude that B. Pertussis/toxin IgG antibodies response is weak in Nigerian children after three doses of DPT (diphtheria, pertussis, and tetanus)/pentavalent vaccination, and there is a rapid decline of antibody levels between 12 and 35 months. We recommend that booster vaccination should be given at 12 to 15 months of age.
Keywords: pertussis; antibody; Nigeria